Particle size-dependent superspin glass behavior in random compacts of monodisperse maghemite nanoparticles. (21st April 2016) - Andersson, Mikael Svante; Mathieu, Roland; Normile, Peter S; Lee, Su Seong; Singh, Gurvinder; Nordblad, Per; Toro, Jose Angel De
Abstract: Dense random assemblies made from highly monodisperse γ -Fe2 O3 nanoparticles with sizes ranging from 6.2 to 11.5 nm have been investigated by DC and AC magnetometry. It is found that all assemblies undergo superspin glass phase transitions. The superspin glass phase transition temperature is strongly dependent on the particle size and the nature of the interparticle interaction. However the transition from superparamagnet to superspin glass, as evidenced by the shape of the ac-susceptibility curves and the dynamic critical exponents associated with the transition, is similar in all systems.